EFFECTIVENESS OF THE METHOD DRILL AND PRACTICE IN IMPROVING BASIC KICKING TECHNIQUES IN KARATE SPORTS - Galih Dwinanda Gumilar; Oman Hadiana (Indonesian Journal of Education Teaching and Learning (IJETL), 2025)
This study aims to analyze the effectiveness of the application of the drill and practice method in improving basic kicking techniques in karate athletes. The research method used is an experiment with a One Group Pretest-Posttest Design , involving 20 karate athletes from the Kuningan Karate School. Data were collected through direct observation, skill tests, and measurements before (pretest) and after (posttest) the training intervention. The results of the descriptive statistical analysis showed an increase in the average value from 65.45 (pretest) to 72.60 (posttest). The normality test (Kolmogorov-Smirnov and Shapiro-Wilk) and homogeneity (Levene's test) ensured that the data were normally distributed and homogeneous (p > 0.05). The paired sample t-test confirmed a significant difference between the pretest and posttest (t (19) = -19.227; p = 0.000), with a mean difference of -7.15 and a 95% confidence interval (-7.928 to -6.372). These findings prove that the drill and practice method significantly improves the basic kicking techniques of karate athletes, especially in terms of speed, accuracy, and strength. The implications of the study support the use of this method in karate training to strengthen muscle memory and movement consistency.